2012
DOI: 10.1088/0957-0233/23/2/025403
|View full text |Cite
|
Sign up to set email alerts
|

The systematic error in digital image correlation induced by self-heating of a digital camera

Abstract: The systematic strain measurement error in digital image correlation (DIC) induced by self-heating of digital CCD and CMOS cameras was extensively studied, and an experimental and data analysis procedure has been proposed and two parameters have been suggested to examine and evaluate this. Six digital cameras of four different types were tested to define the strain errors, and it was found that each camera needed between 1 and 2 h to reach a stable heat balance, with a measured temperature increase of around 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(50 citation statements)
references
References 20 publications
1
49
0
Order By: Relevance
“…As a result, only E4 was recorded by the camera. The digital image correlation (DIC) method (Ji et al, ; Ma et al, ; Pan et al, ; Peters & Ranson, ; Sutton et al, ; Yamaguchi, ; Zhuo et al, , ) was used to compute the displacement field of the sample surface. The two red lines in Figure b, which are symmetric and offset by 4.2 mm from the fault, are each composed of 1,771 pixels (measurement points).…”
Section: Experiments and Methodsmentioning
confidence: 99%
“…As a result, only E4 was recorded by the camera. The digital image correlation (DIC) method (Ji et al, ; Ma et al, ; Pan et al, ; Peters & Ranson, ; Sutton et al, ; Yamaguchi, ; Zhuo et al, , ) was used to compute the displacement field of the sample surface. The two red lines in Figure b, which are symmetric and offset by 4.2 mm from the fault, are each composed of 1,771 pixels (measurement points).…”
Section: Experiments and Methodsmentioning
confidence: 99%
“…The analysis of the influence of subset size on the standard deviation of displacements ( Figure 21) shows the expected dependency on the square root of the number of pixels; however, apart from the significantly larger values, two points should be underlined: the global shape of the various curves is no longer parabolic and shows two peaks in the areas of maximum positional error and a central minimum; moreover, the errors of the cAB 4 and qAB 6 polynomials are no longer significantly smaller than the other kernels showing errors somewhat larger than those of cubic interpolants. 16 As said, the analysis of defocused images and of different types of speckles in low visibility conditions gives similar results to the previously described ones (numerical values are different, but ratios are roughly the same), thus we chose to skip these points.…”
Section: Visibilitymentioning
confidence: 60%
“…In short, self‐heating can cause severe and complex image distortion. Test with six digital cameras conducted by Ma et al showed that the strain error rate is approximately 8 to 20 με° C −1 and the maximum total strain error up to 230 με is large enough to be considerable. In the case of the long‐time operation of the digital camera, it is necessary to preheat the digital camera to the thermal balance stage before the experiment.…”
Section: The Main Error Sources In 2d‐dic Measurementmentioning
confidence: 99%